Superparamagnetic and ferromagnetic behavior of ZnFe2O4nanoparticles synthesized by microwave-assisted hydrothermal method - Anukorn Phuruangrat (2018)
© 2017, Pleiades Publishing, Ltd. Zinc ferrite (ZnFe2O4) nanoparticles were successfully synthesized from Zn(NO3)2· 6H2O and Fe(NO3)3· 9H2O by microwave hydrothermal method at 150°C for 1 h. Cubic ZnFe2O4with particle size below 7 nm was formed in the solution at pH ≥ 6. The crystallinity and particle size of ZnFe2O4nanoparticles were increased after calcination. The effects of pH of the precursor solution and calcination on the particle size and crystallinity of the particles were studied. At room temperature the products show superparamagnetic and ferromagnetic properties, determined by their size. The formation mechanism of ZnFe2O4was also discussed according to the experimental results.